Study of Primate Diversity at the Botanical Garden in Pahlawan Tuanku Tambusai University - Syamsul Bachry; Febri Ayu; Rahmad , Rendi; Novalis, Miki; Primayola, Meilani (Faculty of Agriculture, Tompotika Luwuk University, 2024)
Pahlawan Tuanku Tambusai University has a Botanical Garden with an area of ​​152 Ha with an area of ​​Zone A (27 Ha) and Zone B (125 Ha). The Botanical Garden of Universitas Pahlawan is a habitat for various types of Fauna one of the animals in the Botanical Garden is Primates. This study aims to analyze the diversity of primates in Zone A at the Botanical Garden of Universitas Pahlawan from Kampar, Riau. The research method uses the transect path method by walking along the transect line. Primate research studies in the Botanical Garden area, especially in Zone A, there are three types of primates, namely Macaca fascularis, Presbytis thomasi and Macaca nemestrina. Based on field observations, Presbytis thomasi is the dominant primate, with a count of 14, followed by Macaca fascicularis with a total of 10, and Macaca nemestrina with a total of 2. Primate diversity in the Pahlawan University Botanical Garden remains relatively low, ranging from 0.14 to 0.52, and the dominance index varies from 0.08 to 0.54. The dominant primate is the Kedih (Presbytis thomasi) with a dominance index 0.5. The distribution of the three primates is still in the secondary forest area and part of the rubber and oil palm plantation area of ​​the Pahlawan University Botanical Gardens.